Aradidae from Vietnam II. Longitergus, a new genus and two new species of micropterous Mezirinae (Hemiptera: Heteroptera: Aradidae) - Pham, Minhlan; Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2013)
A new micropterous flat bug genus, Longitergus n.gen. with the species productus n.sp. and similis n.sp. from Vietnam, is described. A key to related Oriental genera is given and the diagnostic morphological characters of the new genus and species are illustrated.